Comparison Of The Effectiveness Of Remdesivir And Favipiravir In Moderate To Critical Covid-19 Patients - Irmi Syafa'ah; Mohammad Fathul Qorib; Filhi Rihmayuwainilla (Jurnal Medika Hutama, 2025)
Introduction: COVID-19 is a respiratory disease outbreak that caused a pandemic in late 2019. COVID-19 causes infected patients to experience mild, moderate, severe to critical respiratory diseases that cause death. However, until now there has been no specific therapy for COVID-19. The most currently used therapy is using antivirals, such as remdesivir and favipiravir. This study aims to analyze the effectiveness of antivirals remdesivir and favipiravir in improving symptoms and duration of treatment of moderate to critical COVID-19 patients at Airlangga University Hospital in May-June 2021. Methods: Observational analytic study with retrospective cohort method obtained from the medical records of moderate to critical COVID-19 patients who used remdesivir and favipiravir antivirals at Universitas Airlangga Hospital. Data were collected using total sampling technique and tested with Mann-Whitney. The parameters used in this study were age, gender, comorbidities, severity, antiviral drugs, and duration of treatment. Results: Of the 130 study subjects, 27 patients used remdesivir and 103 patients used favipiravir. The test results obtained as follows, the test between antivirals and symptom improvement time found p = 0.015 (p < 0.05) which means significant, the test between antivirals and length of treatment found p = 0.018 (p < 0.05) which means significant. Conclusion: There is a significant difference in effectiveness between the use of remdesivir and favipiravir on symptom improvement time and length of treatment for moderate to critical COVID-19 patients at Airlangga University Hospital.